2007
DOI: 10.1088/1742-6596/76/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Data aggregation in wireless sensor networks using the SOAP protocol

Abstract: Abstract. Wireless sensor networks (WSN) offer an increasingly attractive method of data gathering in distributed system architectures and dynamic access via wireless connectivity. Wireless sensor networks have physical and resource limitations, this leads to increased complexity for application developers and often results in applications that are closely coupled with network protocols. In this paper, a data aggregation framework using SOAP (Simple Object Access Protocol) on wireless sensor networks is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Instead, they make decisions whether the information should be stored for future use, relayed as they are, or modified by applying computation and aggregation with other data. 15 The central server has been programmed with two algorithms. First is the threshold based algorithm, which attempts to identify the physiological parameter values that are potentially harmful or indicative of immediate danger to the patients.…”
Section: Implementation and Resultsmentioning
confidence: 99%
“…Instead, they make decisions whether the information should be stored for future use, relayed as they are, or modified by applying computation and aggregation with other data. 15 The central server has been programmed with two algorithms. First is the threshold based algorithm, which attempts to identify the physiological parameter values that are potentially harmful or indicative of immediate danger to the patients.…”
Section: Implementation and Resultsmentioning
confidence: 99%
“…A previous study on the use of SOAP, as a protocol for data aggregation in WSN, has found that there is considerable overhead on the network resources including the transmission and processing of SOAP messages [13]. The study showed that the use of SOAP message has doubled the round trip times of exchanged messages when compared to transmitting and processing raw, unformatted data.…”
Section: Overhead In Soap Messagesmentioning
confidence: 97%
“…where [4,24]. However, everything that is inappropriate about the object-oriented approach inside a WSN is doubly so with a human-readable data format.…”
Section: Neural Networkmentioning
confidence: 99%